PERCEIVED BENEFITS OF CORPORATE SOCIAL RESPONSIBILITY - Monareng, Geraldine Makole (My University, 2011)
Corporate Social Responsibility (CSR) has been found to have different meanings to different communities in different countries. The perception of the benefits derived by various stakeholder groups remains a contentious issue in both academic circles and in application in business and/or politics. The purpose of this research was to analyse the perceived benefits of CSR to different stakeholder groups in South Africa. A single case was opted for in this report. The questionnaire used was targeted at employees from the four collaborating companies in CSR initiatives at Liberty. These were Liberty Life, the Liberty Foundation, the Learning Channel and MindSet Network. The main findings of the research were that the four identified main stakeholder groups (shareholders, customers, employees and the community), all benefited from CSR initiatives undertaken by an organisation. The benefits were found to be both direct and indirect (almost incidental) to all four stakeholders. The benefits were more of a long term nature than would be quantifiable in the short term. The CSR activities undertaken at Liberty through the Foundation could be leveraged further to translate into new business opportunities in existing or new markets for the growth of the group and greater returns to shareholders.
MBA - WBS
Keywords: Corporate social responsibility